Statistical Techniques for Analytical Review in Auditing (Book). - Garstka, Stanley J.; Brief, Richard P. (The Accounting Review, 1987)
Reviews the book "Statistical Techniques for Analytical Review in Auditing," by Kenneth W. Stringer and Trevor R. Stewart.